2021
DOI: 10.4103/jpbs.jpbs_753_20
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Potential of Naturally Occurring Bioactive Secondary Metabolites

Abstract: The use of traditional medicines of natural origin has been prevalent since ancient times globally as the plants produce a great diversity in their secondary metabolites. The naturally occurring bioactive constituents in food and other plant materials have shown widespread attention for their use as alternative medicine to prevent and cure microbial growth with the least toxic manifestations. The inclusion of these contents revealed their crucial role to improve the therapeutic efficacy of the classical drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 116 publications
0
7
0
1
Order By: Relevance
“…The result of the GC/MS study shown in Table 3 revealed the presence of several important compounds, highlighting the detection of specific phenols, alkaloids, terpenes and esters with antibacterial properties [26]. In particular, cyclotrisiloxane-hexamethyl and cyclotetrasiloxane-octamethyl were identified as the predominant compounds in the strains studied, with a particular content in P. kessleri.…”
Section: Resultsmentioning
confidence: 92%
“…The result of the GC/MS study shown in Table 3 revealed the presence of several important compounds, highlighting the detection of specific phenols, alkaloids, terpenes and esters with antibacterial properties [26]. In particular, cyclotrisiloxane-hexamethyl and cyclotetrasiloxane-octamethyl were identified as the predominant compounds in the strains studied, with a particular content in P. kessleri.…”
Section: Resultsmentioning
confidence: 92%
“…Therefore, the search for new antimicrobial natural products continues to draw the attention of many researchers. One of the most influential families of bioactive phytochemicals are polyphenols, which, alongside terpenes, are one of the most abundant groups of secondary metabolites [ 8 ]. The chemical structure of polyphenols includes one hydroxyl group (-OH), responsible not only for the antioxidant properties but also for the antimicrobial ones.…”
Section: Introductionmentioning
confidence: 99%
“…Plant secondary metabolites (PSMs), which are biologically active compounds produced by plants, have gained attention as alternative therapies for various medical conditions [7,8]. These compounds have been shown to have a wide range of pharmacological activities, including anti-inflammatory, antioxidant, and antimicrobial properties [9,10]. They are often used in traditional medicine and are being studied for their potential to treat a variety of health problems, such as infections, inflammation, cancer, and cardiovascular disease [11].…”
Section: Introductionmentioning
confidence: 99%